Concepts and methods to measure societal impacts: An overview - Susanne Bührer; Alexander Feidenheimer; Rainer Walz; Ralf Lindner; Bernd Beckert; Elisa Wallwaey (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2022)
[Introduction] A critical analysis of the topic "societal impacts" is relevant and necessary for several reasons. These are: 1) The topic of societal impacts is currently at the top of the agenda in both (applied) science and in research and innovation (R&I) policy. 2) There is no uniform understanding of what a societal impact is in the literature. Definitions of societal impacts often refer to other impact dimensions (RRI, policy impacts, SSH impacts, cul-tural impacts, health impacts and sustainability indicators). 3) There is a great deal of confusion surrounding the topic of societal impacts. It has references to (1) impact measurement (Theory-based impact evaluation (TBIE), Theories of Change (ToCs), I-O-O-I (Input-Output-Outcome-Impact) models, impact pathways, participatory im-pact pathways, public value mapping, payback framework), (2) other discourses such as mis-sion orientation and addressing the Sustainable Development Goals (SDGs), and (3) questions concerning research assessment (responsible metrics, metrics tide, the Leiden manifesto). - This report addresses these challenges as follows: We present the different definitions of societal impacts in the next chapter (chapter 2.1) and the different strands of discourse that contribute to the societal impacts topic. We distinguish the discourses on societal impact in a narrower sense (chapter 2.2) from related discourses (chapter 2.3). The paper closes with some conclusions (chapter 3). Please note: This report concentrates on research funding and therefore excludes the societal im-pacts that (can) come about through sectoral policies. Second, following the logic of programme evaluations, we primarily adopt an ex post perspective, although we know that societal impacts (can) play an important role in ex ante impact assessments as well. Finally, it was not (yet) examined to what extent interaction effects occur between the different impact areas.
Keywords: 330